URBAN LEFT-OVER SPACE: CHARACTERISTIC IDENTIFICATION OF THE IN-BETWEEN SPACES IN RIVERSIDE SETTLEMENT (CASE STUDY: MARTAPURA RIVERSIDE SETTLEMENT AT SASIRANGAN VILLAGE) - Juleta Nadea Anilaputri; Syam Rachma Marcillia (Built Environment Studies, 2023)
The identity of "Thousand Rivers' City" makes the river have the meaning of identity and life orientation. River-oriented life inflicted an adaptive behavior called budaya sungai. However, the globalization process has caused a shift from river-oriented to land-oriented and creates heterogeneity in riverside settlements. Creating variations of typology such as atas sungai, bantaran sungai, and tepian sungai. The emergence of these typologies indirectly creates urban leftover space as a transition called the in-between space. This research aims to identify the characteristic of the in-between spaces in riverside settlements so that the space does not become negative and can be utilized to meet the living needs of people who live in riverside settlements. The research used explanatory sequential design methods, based on the quantitative phase, a figure-ground analysis identified curvilinear as the typological patterns and homogenous as textural patterns of the riverside settlement. The map shows a high-density level of solids with no central open system void. Based on the qualitative phase, all in-between spaces have linear patterns and are mostly made of wood materials. 76.47% of enclosures are open but in contrast to land use which is mostly private. 2 out of 17 in-between spaces could not be characterized.